Activation of endogenous arginine vasopressin neurons inhibit food intake: by using a novel transgenic rat line with DREADDs system. Issue 1 (December 2017) - Yoshimura, Mitsuhiro; Nishimura, Kazuaki; Nishimura, Haruki; Sonoda, Satomi; Ueno, Hiromichi; Motojima, Yasuhito; Saito, Reiko; Maruyama, Takashi; Nonaka, Yuki; Ueta, Yoichi
Abstract Various studies contributed to discover novel mechanisms of central arginine vasopressin (AVP) system responsible for the behaviour albeit endogenous vasopressin activation. We established a novel transgenic rat line which expresses both human muscarinic acetylcholine receptors (hM3Dq), of which ligand is clozapine-N-oxide (CNO), and mCherry fluorescence specifically in AVP neurons. The mCherry neurons that indicate the expression of the hM3Dq gene were observed in the suprachiasmatic (SCN), supraoptic (SON), and paraventricular nuclei (PVN). hM3Dq-mCherry fluorescence was localized mainly in the membrane of the neurons. The mCherry neurons were co-localized with AVP-like immunoreactive (LI) neurons, but not with oxytocin-LI neurons. The induction of Fos, which is the indicator for neuronal activity, was observed in approximately 90% of the AVP-LI neurons in the SON and PVN 90 min after intraperitoneal (i.p.) administration of CNO. Plasma AVP was significantly increased and food intake, water intake, and urine volume were significantly attenuated after i.p. administration of CNO. Although the detailed mechanism has unveiled, we demonstrated, for the first time, that activation of endogenous AVP neurons decreased food intake. This novel transgenic rat line may provide a revolutionary insight into the neuronal mechanism regarding central AVP system responsible for various kind of behaviours.